2017
DOI: 10.1111/cxo.12488
|View full text |Cite
|
Sign up to set email alerts
|

Soft multifocal simultaneous image contact lenses: a review

Abstract: Soft multifocal simultaneous image contact lenses have boomed in recent years due to the growing number of presbyopic patients demanding visual solutions, allowing them to maintain their current standard of living. The concept of ‘simultaneous image’ is based on blur interpretation and/or blur tolerance of superimposed multiple images on the retina formed by various powers of a contact lens. This is the basis for a specific type of multifocal contact lens developed for the compensation of presbyopia. Manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 124 publications
4
37
0
Order By: Relevance
“…From these epidemiological data and considering that the most prevalence condition related with ageing is presbyopia [16], there are many patients worldwide in which both presbyopia and DED co-exist. Currently, multifocal contact lenses (MCLs) [17,18] and multifocal intraocular lenses (IOLs) [19] are both well-established and an effective way to compensate the presbyopia, reducing spectacle dependency. The ocular surface changes related to ageing may adversely affect the optical quality of the eye and could have a detrimental effect on the success of these treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these epidemiological data and considering that the most prevalence condition related with ageing is presbyopia [16], there are many patients worldwide in which both presbyopia and DED co-exist. Currently, multifocal contact lenses (MCLs) [17,18] and multifocal intraocular lenses (IOLs) [19] are both well-established and an effective way to compensate the presbyopia, reducing spectacle dependency. The ocular surface changes related to ageing may adversely affect the optical quality of the eye and could have a detrimental effect on the success of these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of IOL implantation, optimal pre-surgical ocular conditions are required in order to avoid risks such as severe DED, inaccurate IOL power estimation [20] and ocular discomfort after IOL [21]. Despite the fact that most of the research studies conducted until now have demonstrated that MCLs provide good visual quality results [17,[22][23][24][25][26][27], the prescription rate [28,29]) is low. Although many factors could be behind this low adherence, it should be noted that the CLs materials are the same as monofocal CLs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows different examples of multifocal contact lens designs. ese design concepts work under two different principles [9,32,36]: (i) alternating image, in which a translating movement of the lens when looking downwards results in viewing through an area with a different refractive power; and (ii) simultaneous image, where the simultaneous projection of the images coming from multiple target distances are presented to the eye at the same time at different focal planes. en, in the simultaneous image, there must be a neural adaptation to select the sharp image depending on the visual target.…”
Section: Bifocal and Multifocal Contact Lensesmentioning
confidence: 99%
“…In this review article, we present an overview of the recent developments of bifocal and multifocal contact lens designs for the correction of presbyopia and myopia control, including the optical design of different platforms for bifocality and multifocality, computational simulations and performance assessment, and their connection with the visual performance, patient acceptance, and efficacy. For further information on the performance of earlier designs for presbyopia correction [1,9] and myopia control, including orthokeratology [10,11], the reader must consult the abundant existing literature including several systematic reviews and meta-analyses on the former topic [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The nominal distance‐vision power and addition is the only information available regarding the optical power of MCLs. The power profile of MCLs has been demonstrated to report important information that could be used during the fitting process …”
mentioning
confidence: 99%